External and Internal Irreversibility: Heat Engine as an Example - Sarkar A.; Mondal S.S. (My University, 2025)
The article attempts to clarify the meaning of internal and external irreversibility using the example of a heat engine. It has been proved that the efficiency of an internally reversible but externally irreversible engine is almost 50% of the efficiency of a totally reversible engine. © 2018, Indian Academy of Sciences.